Numerical modelling to study the effect of DC electric field on a laminar ethylene diffusion flame. (March 2021) - Sayed-Kassem, Ahmad; Elorf, Abdallah; Gillon, Pascale; Idir, Mahmoud; Sarh, Brahim; Gilard, Virginie
Abstract: An applied DC electric field was experimentally demonstrated to modify the flame structure and gas dynamic in an ethylene diffusion flame. The aim of this paper is to investigate the influence of the electric field on the flow field and its impacts on the flame behavior. A numerical study has been performed to elucidate the experimental observations and to monitor the effect of electric body force on the flame. The numerical model was validated by comparing the computed results to experimental measurements from the literature. The resulting computed flame shape was compared to a visible image taken during the experiment. The simulated OH mole fraction, the burning rate and the computed velocity and temperature are presented. The developed model proved the ability to reproduce qualitatively the experimental flame behavior when submitted to the electric field. The electric field is shown to modify the flame shape (flame tip, flame shortness and flame deformation), to promote the burning process and to improve the ion production. Results show that the modifications are due to an air entrainment acting specifically near the burner zone enhancing the mixture and changing the fluid dynamic in this region. The ionic wind is demonstrated to increase the maximum burning rate and promoting ions' formation mostly near the burner. A more detailed model (detailed ions' chemistry and soot model with charged particles, detailed electric diffusion) is necessary to gain a better understanding of the influence of electric field on diffusion combustion and soot formation. Highlights: A numerical model was developed to simulate ethylene diffusion combustion and validated with experimental measurements. The developed model was extended to cover the effect of a DC electric field on ethylene non-premixed combustion. An applied electric field deforms the flame structure, promotes the combustion rate and modifies flame dynamic. Ionic wind is responsible for the observed modifications acting essentially near the burner exit.